Reduction of Stabilin-2 Contributes to a Protection Against Atherosclerosis - Kayashima, Yukako; Clanton, Connor A.; Lewis, Amanda M.; Sun, Xinghui; Hiller, Sylvia; Huynh, Phillip; Wilder, Jennifer; Hagaman, John; Li, Feng; Maeda-Smithies, Nobuyo; Harris, Edward N. (Frontiers in Cardiovascular Medicine, 2022)
We have previously identified a novel atherosclerosis QTL, Arch atherosclerosis 5 (Aath5), on mouse chromosome 10 by three-way QTL analyses between Apoe−/− mice on a DBA/2J, 129S6 and C57BL/6J background. The DBA/2J haplotype at the Aath5 locus was associated with smaller plaque size. One of the candidate genes underlying Aath5 was Stabilin-2 (Stab2), which encodes a clearance receptor for hyaluronan (HA) predominantly expressed in liver sinusoidal endothelial cells (LSECs). However, the role of Stab2 in atherosclerosis is unknown. A congenic line of Apoe−/− mice carrying Aath5 covering the Stab2DBA allele on a background of 129S6 confirmed the small reductions of atherosclerotic plaque development. To further determine whether Stab2 is an underlying gene for Aath5, we generated Stab2−/−Apoe−/− mice on a C57BL/6J background. When fed with a Western diet for 8 weeks, Stab2−/−Apoe−/− males developed approximately 30% smaller plaques than Stab2+/+Apoe−/− mice. HA was accumulated in circulation but not in major organs in the Stab2 deficient mice. STAB2-binding molecules that are involved in atherosclerosis, including acLDL, apoptotic cells, heparin and vWF were not likely the direct cause of the protection in the Stab2−/−Apoe−/− males. These data indicate that reduction of Stab2 is protective against atherosclerotic plaque development, and that Stab2 is a contributing gene underlying Aath5, although its effect is small. To test whether non-synonymous amino acid changes unique to DBA/2J affect the function of STAB2 protein, we made HEK293 cell lines expressing STAB2129 or STAB2DBA proteins, as well as STAB2129 proteins carrying each of five DBA-unique replacements that have been predicted to be deleterious. These mutant cells were capable of internalizing 125I -HA and DiI-acLDL similarly to the control cells. These results indicate that the amino acid changes unique to DBA/2J are not affecting the function of STAB2 protein, and support our previous observation that the reduced transcription of Stab2 in the liver sinusoid as a consequence of the insertion of a viral-derived sequence, intracisternal A particle, is the primary contributor to the athero-protection conferred by the DBA/2J allele.